Description of Students' Critical Thinking Skills After Implementing the Problem Posing Model Assisted by PheT in Distance Learning - Roudhoutul Aulia Rochim; Noer Af’idah; Desi Wulandari (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2024)
Objective: The primary objective of this research is to assess the development of critical thinking skills after implementing the PhET-assisted problem-posing learning model in distance education. Method: This study adopts a pre-experimental approach with a one-shot case study design. The study sample comprises 18 students enrolled in the 2023 cohort of the UNHASY Natural Science Education study program. Results: The findings indicate that the average critical thinking score is 79.86, falling within the high category. The distribution of students' critical thinking skills across various categories revealed that 44% belong to the highest category. Notably, the proportions of critical thinking skill indicators are exclusively concentrated in the medium, high, and very high categories, with no instances falling into the low categories. These results underscore the efficacy of employing the PhET-assisted problem-posing learning model as a viable strategy for enhancing students' critical thinking abilities. Novelty: The researcher chose the PhET-assisted problem-posing model, one of the media based on information and communication technology in the form of a virtual laboratory regarding critical thinking skills.